Women in the Informal Sector: Home-based Workers in Karachi (The Pakistan Development Review, 1989)
The exceedingly low official estimates of female labour force participation rates (which range from 3 percent in the 1981 Census to 11 percent in the Labour Force Survey 1986-87) are known to omit a large degree of employment of women in informal sector jobs. Underestimation of female employment tends to be particularly high in case of women working in their homes who are (a) unlikely to admit to working for remuneration and (b) unlikely to be located in labour force surveys or censuses with male enumerators. These home-based workers are thought to comprise a large proportion of the "hidden" female labour force in Pakistan and their study becomes a most interesting supplement to existing official statistics. The study of home-based workers is based on the findings of a survey of 1000 married women undertaken in Karachi in 1987. The sample of 680 working and 320 non-working women covered a whole range of social and income classes. 1 Among the 680 working women was included the sub-sample of 470 low income working women of which 247 were home-based workers. Combined information on women and their households were collected through a faidy lengthy questionnaire: the interview schedule comprised questions on earnings, ethnic affiliation, education, age, sex and occupation of all household members, division of domestic responsibilities, and employment histories of individual women. Specially trained female enumerators were employed to explore the income-earning activities of women in each household even where there may be initial reluctance to admit that female members do any work for remuneration.